Polar low research: recent developments and promising courses of research - Marta Moreno-Ibáñez; Marta Moreno-Ibáñez (Frontiers in Earth Science, 2024)
Polar lows (PLs) are intense maritime mesoscale weather systems that develop during marine cold air outbreaks at high latitudes. The objective of this review is to describe the advances in polar low research since the last literature review—published 3 years ago—, indicate the knowledge gaps that remain, and suggest promising courses of research. Among the breakthroughs identified here are the first climatology of PLs obtained with a global atmospheric model, and increased evidence showing that baroclinic instability is the main mechanism leading to PL development. Despite these advances, many challenges persist such as the lack of conventional observations of PLs and the need to better understand coupled atmosphere-ocean processes involved in PL development. With the rapid advances in deep learning, this method has the potential to be used for PL forecasting.